Four decades of the morphological dynamics of the lakes in the Jianghan Plain using Landsat observations. (22nd April 2017) - Shi, Yumin; Feng, Lian; Gong, Jianya
Abstract: Using four decades of Landsat observations between 1978 and 2014, we documented and studied the long‐term dynamics of the inundation conditions in the Jianghan Plain, Central China. Three morphological factors, including inundation areas, perimeters and shoreline developments (SDs), of the 51 selected lakes were calculated. Significant long‐term morphological changes were found in lakes in the Jianghan Plain. The total area dramatically increased from 838.0 km 2 in 1978 to 1200.8 km 2 in 1989, and an overall decreasing trend was observed in the later period. The changing patterns of the perimeters and SDs were different from the inundation areas, especially for the largest lake in this area (Honghu). The inconsistent changes between the inundation area and the other two morphological parameters were likely caused by increasing human activities. This study demonstrated the importance of remote sensing in obtaining multi‐decadal lake changes in terms of both the inundation area and the morphological complexity.